Pengaruh Kualitas Produk terhadap Keputusan Pembelian di Toko Moro Bootwear Jambi - Miswanto; Ade Irma; Endah Trikurniasih (Haka Vyza Media, 2025)
This study aims to determine the extent to which product quality influences consumer purchasing decisions at the Moro Bootwear Store in Jambi. The approach used was quantitative, using descriptive and associative methods. The sampling technique used was accidental sampling, with 68 respondents, and data processing was performed using IBM SPSS version 25 software. The results of the validity and reliability tests indicated that all instruments used in the questionnaire were valid and reliable. The Pearson correlation test yielded a value of 0.712, indicating a strong and positive relationship between product quality and purchasing decisions. The coefficient of determination (R²) of 0.507 indicates that 50.7% of the purchasing decision variables can be explained by product quality. Furthermore, the t-test results showed a calculated t-value of 8.240 with a significance level of 0.000 <0.05, indicating that product quality significantly influences purchasing decisions. Based on these results, it can be concluded that product quality plays a significant role in influencing consumer purchasing decisions. Therefore, the manager of the Moro Bootwear Jambi Shop is advised to continue to improve product quality aspects such as design, comfort, durability, and raw materials in order to maintain consumer loyalty and increase business competitiveness.